Receipt of the authorization letter of work order for the acknowledgement of BUCG - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding receipt of the authorization letter of work order for the acknowledgement of BUCG for BRAC University new campus project.